PENERJEMAHAN INTERJEKSI BAHASA JEPANG KE DALAM BAHASA INDONESIA (STUDI KASUS PADANAN TERJEMAHAN PADA KOMIK ONE PIECE) - Tria Rahmadani Putri; Arza Aibonotika; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : This study is about interjections translation in One Piece comic. The purpose of this study is to examines interjections and describes the procedures and method of translation based on Newmark theory, and analyze the equivalences of Japanese interjections into Indonesian language. The data of this study were analyze using qualitative descriptive method. The results of this study found 14 interjections using the semantic translation method, and 3 translation procedures, that is componential analysis translation, through translation, and naturalisation translation.Key Word: Interjection, Translation, Comic